KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN ANDONG, DESA DASAN BARU, KECAMATAN KOPANG, KABUPATEN LOMBOK TENGAH - Windi Aulia Putri; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Andong Hamlet is one of the hamlets located in Dasan Baru Village, Kopang District. This study was conducted using an observational method. Based on the results, it was found that homegarden plants in Andong Hamlet, Dasan Baru Village, Kopang District have a Shannon-Wiener diversity index (H’) of 2.08, indicating moderate diversity, moderate distribution, and moderate community stability. This study aims to examine and analyze the diversity of homegarden plant species in Andong Hamlet, Dasan Baru Village, Kopang District, Central Lombok Regency. The method used was direct observation of community homegardens, and the data were analyzed using the Shannon-Wiener diversity index. The results showed that the diversity index (H’) value of 2.08 falls into the moderate category, with moderate distribution and community stability. The plant species identified consist of food crops, fruit plants, medicinal plants, and ornamental plants, all of which provide various benefits to the local community. Therefore, homegardens play an important role in supporting biodiversity and fulfilling the livelihood needs of the local community.